A carbazole based "Turn on" fluorescent sensor for selective detection of Hg2+ in an aqueous medium. Issue 27 (26th February 2016) - Kala, K.; Manoj, N.
Abstract : A colorimetric and fluorescent Hg 2+ selective sensor based on carbazole-barbituric acid conjugate (CBA) is developed. It exhibited visual colour change and a turn-on emission at 593 nm and is selective and sensitive for Hg 2+ in aqueous medium. Abstract : We developed a multimode Hg 2+ selective sensor system based on carbazole-barbituric acid conjugate (CBA). Its colorimetric and fluorescent behavior for Hg 2+ ions in aqueous medium was investigated. Upon Hg 2+ binding, CBA exhibited significant change in the absorption spectrum along with an enhanced emission at 593 nm. This allows the selective and sensitive detection of Hg 2+ without any interference from other metal ions.